2021
DOI: 10.1021/acsanm.0c03156
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Copper Species on the Combustion of Dichloromethane over Cu/HZSM-5 Zeolite Nanoporous Catalysts

Abstract: This study compared the reaction behaviors of dichloromethane (DCM) catalytic combustion over Cu/HZSM-5 (H form of Zeolite Socony Mobil-5) nanoporous catalysts at different copper loadings. Among the samples investigated, Cu/HZSM-5 with 2.5 wt % Cu showed the best stability with a 90% DCM conversion at 320 °C during a 3 h reaction run. The analysis of the results showed different copper species (including cations and oxides particles) accounted for the diverse reaction behaviors observed. With a low copper loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 48 publications
1
23
0
Order By: Relevance
“…The emission of volatile organic compounds (VOCs) is known to cause ozone layer depletion and photochemical smog formation . Catalytic combustion is considered to be one of the most effective strategies because it is highly adaptable to a broad range of VOC gas concentrations, free of secondary pollution, and able to be run at mild reaction temperatures. Light alkanes (C2–C4) contribute a large fraction of the VOC emissions, particularly ethane and propane, which make up 3.9 and 2.6% of the total VOC emissions, respectively . However, these short-carbon-chain molecules are thermodynamically and chemically stable, making them difficult to catalytically convert. , With the increase of interest in using propane as a fuel in the transportation sector, it is critical to design a robust and economical catalyst that can operate at mild temperatures to control light-alkane oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…The emission of volatile organic compounds (VOCs) is known to cause ozone layer depletion and photochemical smog formation . Catalytic combustion is considered to be one of the most effective strategies because it is highly adaptable to a broad range of VOC gas concentrations, free of secondary pollution, and able to be run at mild reaction temperatures. Light alkanes (C2–C4) contribute a large fraction of the VOC emissions, particularly ethane and propane, which make up 3.9 and 2.6% of the total VOC emissions, respectively . However, these short-carbon-chain molecules are thermodynamically and chemically stable, making them difficult to catalytically convert. , With the increase of interest in using propane as a fuel in the transportation sector, it is critical to design a robust and economical catalyst that can operate at mild temperatures to control light-alkane oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…To further investigate the surface acidity or alkalinity and redox ability of the Cu-VWT catalyst, H 2 -TPR and a series of TPD (O 2 -TPD, NH 3 -TPD, and NO-TPD) tests were performed. For H 2 -TPR (Figure S11b), the reduction peak at 234 °C corresponds to the reduction of isolated Cu 2+ to Cu + , those at 263 °C and 312 °C correspond to the reduction of Cu 2+ in crystalline CuO, and that at 375 °C corresponds to the reductions V 5+ → V 4+ and Cu + → Cu . All of the reduction peaks of Cu-VWT were more intense than those of VWT and appeared at lower temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…For H 2 -TPR (Figure S11b), the reduction peak at 234 °C corresponds to the reduction of isolated Cu 2+ to Cu + , those at 263 °C and 312 °C correspond to the reduction of Cu 2+ in crystalline CuO, and that at 375 °C corresponds to the reductions V 5+ → V 4+ and Cu + → Cu. 40 All of the reduction peaks of Cu-VWT were more intense than those of VWT and appeared at lower temperatures. The H 2 -TPR results thus showed that the Cu-VWT catalyst had a superior redox ability to that of the VWT catalyst.…”
Section: Catalytic Activity Measurementsmentioning
confidence: 94%
“…The absorption of the UV region (208 nm) might be due to the charge-transfer band of O zeolite → Cu + /Cu 2+ related to isolated copper ions in the inner zeolite framework and the peak at 224 nm could be attributed to oligomeric copper oxides (Cu–O–Cu complex) . The band at 780 nm was assigned to d–d transition Cu 2+ ions in the pseudo-octahedral environment such as Cu­(H 2 O) 6 2+ . , The Ce 5 /ZSM-5 sample exhibited two bands (217 and 320 nm), which were attributed to O 2– → Ce 3+ and O 2– → Ce 4+ charge transfers of ceria species, respectively. With the addition of ceria, a new band at about 460 nm appeared for the Cu x Ce y /ZSM-5 catalyst, which could be attributed to the three-dimensional Cu + cluster in the CuO matrix . In addition, the band at 654 nm was assigned to the d–d transitions of Cu 2+ in a distorted O h (square planar) configuration, which belonged to bulk CuO species .…”
Section: Resultsmentioning
confidence: 99%
“…42 The band at 780 nm was assigned to d−d transition Cu 2+ ions in the pseudooctahedral environment such as Cu(H 2 O) 6 2+ . 43,44 The Ce 5 / ZSM-5 sample exhibited two bands (217 and 320 nm), which were attributed to O 2− → Ce 3+ and O 2− → Ce 4+ charge transfers of ceria species, respectively. 45−47 With the addition of ceria, a new band at about 460 nm appeared for the Cu x Ce y /ZSM-5 catalyst, which could be attributed to the three-dimensional Cu + cluster in the CuO matrix.…”
Section: Characterizations For Physical Properties and Chemicalmentioning
confidence: 99%